1994
DOI: 10.1128/iai.62.10.4208-4218.1994
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and sequencing of the cDNA and gene for a novel elastinolytic metalloproteinase from Aspergillus fumigatus and its expression in Escherichia coli

Abstract: An extracellular elastinolytic metalloproteinase, purified from Aspergillus fumigatus isolated from an aspergillosis patient/and an internal peptide derived from it were subjected to N-terminal sequencing. Oligonucleotide primers based on these sequences were used to PCR amplify a segment of the metalloproteinase cDNA, which was used as a probe to isolate the cDNA and gene for this enzyme. The gene sequence matched exactly with the cDNA sequence except for the four introns that interrupted the open reading fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(18 citation statements)
references
References 53 publications
1
17
0
Order By: Relevance
“…A. fumigatus possesses two elastases, one a serine protease and the other a metalloproteinase, both of which have been cloned and sequenced (143,193,200,202,203,266,269,280,281). The serine protease appears to be identical to a previously described 32-kDa alkaline protease (143,200,202,203,269,280,281).…”
Section: Aspergillus Speciesmentioning
confidence: 85%
See 1 more Smart Citation
“…A. fumigatus possesses two elastases, one a serine protease and the other a metalloproteinase, both of which have been cloned and sequenced (143,193,200,202,203,266,269,280,281). The serine protease appears to be identical to a previously described 32-kDa alkaline protease (143,200,202,203,269,280,281).…”
Section: Aspergillus Speciesmentioning
confidence: 85%
“…Antibodies had no effect in an immunosuppressed-mouse model but protected immunocompetent mice given a massive inoculum of conidia. Compared with the serine protease, the role of the A. fumigatus metalloproteinase as a putative virulence factor has not been exten-sively studied (193,266). Immunogold electron microscopy revealed that A. fumigatus organisms invading neutropenic mouse lungs secrete this metalloprotease (193).…”
Section: Aspergillus Speciesmentioning
confidence: 99%
“…These locations are in agreement with those described for certain genes from other Aspergillus spp. (5,38).…”
Section: Identification Of a Nidulans Antigens Consistently Recognizmentioning
confidence: 99%
“…However, in the protease‐deficient mutants created by disruption of the Alp gene (‘gene knockout’) no alteration of virulence in comparison to the wild‐type strains and revertants could be found [ 8, 9]. Later on an extracellular zinc‐containing metalloprotease Mep was isolated [ 10, 11] and the structure of the respective gene described [ 12, 13]. However, in the double disruptant alp‐mep‐ (that was devoid of proteolytic activity on standard media) no decrease in virulence was found [ 12].…”
Section: Introductionmentioning
confidence: 99%